1981
DOI: 10.1590/s0037-86821981000100004
|View full text |Cite
|
Sign up to set email alerts
|

Estado actual de nuestros conocimientos sobre la enfermedad de chagas en la Republica Mexicana

Abstract: Renato Z a r a te * * e Lauren Z a ra te * * Se presentan los datos obtenidos de Ia revisión minuciosa en relación a enferm edad de IN TRO DUCCIONDesde Ia últim a revisión sobre enfermedad de Chagas publicada en México por Biagi y cols. en 1964 11 hasta Ia fecha, aunque son pocos los estúdios realizados sobre el tema, ya se han interessado un número m ayor de investigadores y han aparecido en Ia Literatura Médica Nacional, reportes de hallazgos sobre Ia tripanosomiasis antes m encionada1' 28. Como esta Ifnea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 6 publications
1
13
0
1
Order By: Relevance
“…The proximity to Mexico City makes Morelos state an ideal region for studying Chagas disease. It is also important to note that the northern states now appear to have more human cases, as well as new records of vectors and wild reservoirs (Tay et al 1992, AlejandreAguilar et al 1993, Rangel-Flores et al 2001.…”
Section: Discussionmentioning
confidence: 99%
“…The proximity to Mexico City makes Morelos state an ideal region for studying Chagas disease. It is also important to note that the northern states now appear to have more human cases, as well as new records of vectors and wild reservoirs (Tay et al 1992, AlejandreAguilar et al 1993, Rangel-Flores et al 2001.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] A few entomological studies of the triatomine vectors have been carried out and have reported that 39 species of triatomine bugs were present in Mexico, of which 20 have been found naturally infected by T. cruzi, 34,35 3 Prevalence of infection ranging from 16-18% for domiciliary T. dimidiata in Yucatán, 36 to 33% for T. barberi, 50% for T. p. mazzotti and 18% for T. p. longipennis in Jalisco, 37 and up to 70-92% for T. barberi and 90% for T. p. pallidipennis in Morelos 35,38 have been reported. Feeding habits of some species such as T. dimidiata and T. barberi have been determined and include humans as a relatively frequent feeding source, 36,39,40 clearly demonstrating the vectorial capacity of these species.…”
Section: Chagas' Disease In Mexicomentioning
confidence: 99%
“…There are 32 species of arthropod vectors for T. cruzi in Mexico, distributed throughout the country, and the endemic area for these vectors covers two-thirds of the Mexican territory; among them, the main intradomiciliary species are Triatoma barberi in 12 States, and Triatoma dimidiata in 16 (Tay et al 1981;Salazar-Schettino et al 2010).…”
Section: Introductionmentioning
confidence: 99%